How to Become a Clinical Psychologist - Golding, Laura, author; Moss, Judith, 1969-, author (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis, 2019)
How to Become a Clinical Psychologist provides a clear overview of a career in clinical psychology, with chapters examining areas such as the educational and work experience requirements for selection, the doctoral training programmes and the personal qualities and attributes necessary for the profession. The training process is described and the wide range of career options post-qualification are outlined, supported with testimonials and first-hand accounts from clinical psychologists, current trainees and those aspiring to this career. Practical advice and examples are given throughout the guide and a wide range of real-life examples bring the realities of this challenging yet rewarding career to life.